Provenance research today : principles, practice, problems - Tompkins, Arthur; Tompkins, Arthur (Lund Humphries in association with IFAR, 2020)
This is the first accessible reference handbook to cover key aspects of provenance research for the international art market. It guides the reader from a basic introduction to research methods to questions of ethics and the challenges of specific case histories and contexts. Provenance research is a crucial component of any art-market transaction. Without a provenance it is often difficult to establish a work's authenticity, its true value, or who has legal title. Whether buying, selling, or simply maintaining an artwork in either a private or a public collection, the days when a blind eye could be turned to the history (or the lack of a known history) of a work have long gone. Proper, thorough, and effective provenance research is the minimum required and demanded in today's art world - a world that is increasingly recognizing the need for greater and more effective self-regulation in the face of fakes, forgeries, and challenges to ownership or authenticity that are now commonplace. 'The Provenance Research Handbook' is the essential reference tool for anyone involved in the art world, including provenance researchers, owners, or would-be owners, sellers of artworks, galleries, auction houses, collectors, dealers, museums, galleries, police, and art lawyers.